Development of Biogas Technology for KHDTK Wanagama I Communities - Rini Pujiarti; Johanes Pramana Gentur Sutapa; Sigit Sunarta; Ganis Lukmandaru; Denny Irawati; Rizki Arisandi; Yudhistira Adyatama; Farahdhila Yasmin Al-Husna (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: KHDTK Wanagama I have strong interactions with surrounding communities, many of whom rely on cattle farming.  However, many farmers have not adequately considered the environmental pollution impacts associated with cattle farming activities. Therefore, an alternative utilization of organic waste in the form of cow manure was implemented through biogas production, which can be used as a household-scale fuel. Contribution: This study contributes by integrating technical redesign of small-scale biogas system with a participatory community-based approach, supported by measurable performance indicators. This study evaluates system performance, durability improvement, and practical usability, providing a replicate model for sustainable rural biogas implementation. Method: A participatory action research approach was applied through baseline surveys, stakeholder coordination, biogas system redesign, technical implementation, and performance evaluation using technical and social indicators. Results: The system produced approximately 0.20 m3/day of biogas from one cow, with a digester capacity of 2.01 m3 and a loading period of about 10 days. This output enables 45-50 minutes of daily cooking, indicating that the system technically feasible for basic household energy needs in small scale rural settings. Conclusion: Through this community service activity, it is expected that a fostered village and biogas demonstration site utilizing cow manure can be established and utilized by the community for household or group needs, as well as serve as an environmental education site for learning about environmentally friendly alternative energy.